Performance enhancement with supplements: incongruence between rationale and practice - Mazanov Jason; Naughton Declan P; Petróczi Andrea; Holloway Allison; Bingham Jerry (Taylor & Francis Group, 2007)
Abstract Background Athletes are expected to consider multiple factors when making informed decision about nutritional supplement use. Besides rules, regulations and potential health hazards, the efficacy of different nutritional supplements in performance enhancement is a key issue. The aim of this paper was to find evidence for informed decision making by investigating the relationship between specific performance-related reasons for supplement use and the reported use of nutritional supplements. Methods The 'UK Sport 2005 Drug Free Survey' data (n = 874) were re-analysed using association [χ2] and 'strength of association' tests [ϕ] to show the proportion of informed choices and to unveil incongruencies between self-reported supplement use and the underlying motives. Results Participants (n = 520) reported supplement use in the pattern of: vitamin C (70.4%), creatine (36.1%), whey protein (30.6%), iron (29.8%), caffeine (23.8%), and ginseng (8.3%) for the following reasons: strength maintenance (38.1%), doctors' advice (24.2%), enhancing endurance (20.0%), ability to train longer (13.3%), and provided by the governing body (3.8%). Of thirty possible associations between the above supplements and reasons, 11 were predictable from literature precedents and only 8 were evidenced and these were not strong (ϕ < .7). The best associations were for the ability to train longer with creatine (reported by 73.9%, χ2 = 49.14, p < .001; ϕ = .307, p < .001), and maintaining strength with creatine (reported by 62.6%, χ2 = 97.08, p < .001; ϕ = .432, p < .001) and whey protein (reported by 56.1%, χ2 = 97.82, p < .001; ϕ = .434, p < .001). Conclusion This study provided a platform for assessing congruence between athletes' reasons for supplement use and their actual use. These results suggest that a lack of understanding exists in supplement use. There is an urgent need to provide accurate information which will help athletes make informed choices about the use of supplements.